Synthesis and characterization of cerium doped NiZn nano ferrites as substrate material for multi band MIMO antenna - Asif, Raees Muhammad; Aziz, Abdul; Akhtar, Majid Niaz; Khan, Muhammad Azhar; Abbasi, Muhammad Nawaz; Abdul Muqeet, Hafiz (PLOS ONE, 2024)
In addressing issues related to electromagnetic interference, the demand for ferrite materials with exceptional magnetic and dielectric properties has escalated recently. In this research, sol-gel auto combustion technique prepared Nickel zinc ferrites substituted with cerium, denoted as Ni0.5Zn0.5Ce0.02Fe1.98O4.X-ray diffraction (XRD), Vibrating Sample Magnetometer (VSM), and Field Emissions Scanning Electron Microscope (FESEM) were used to investigate the structure, magnetic properties, and morphology of Cerium doped NiZn Nano ferrites, respectively. The magnetic and dielectric properties of the sample was examined within a frequency range of 2.5–5.5 GHz. Sample exhibits low permittivity (2.2), high permeability (1.4), low dielectric (0.35) and magnetic loss tangent (-0.5) and highest saturation magnetization measuring 30.28 emu/g. A Novel Double-band, 4x4 MIMO window grill-modeled antennas operating on 3.5 GHz and 4.8 GHz frequency bands for 5G smartphones is designed using the CST microwave studio suite. The performance of window grilled 4x4 MIMO antenna model with Cerium doped NiZn nano ferrites as substrate, is investigated and found the return loss of -35 and -32 dB, with the bandwidth of 200MHz, gain (1.89 & 4.38dBi), envelope correlation coefficient (0.00185), channel capacity loss (0.2bps/Hz), and interterminal isolation of (22& 19dB).The results show that the antenna size is reduced with improved bandwidth, higher isolation and better diversity gain performance using Cerium doped NiZn nano ferrite substrate compared to conventional dielectric substrates.